Physical activity and learning after school the PAL program - Schwanenflugel, Paula J.; Tomporowski, Phillip D. (The Guilford Press, 2018)
"Every school day, more than 10 million children attend after-school programs in the United States. This book provides a research-based blueprint for offering students in grades 1-5 innovative programming that combines intensive physical activity and social-emotional skills development with academic enrichment in reading, mathematics, and social studies. Presented is an integrative approach that has been developed and tested in high-poverty schools. The volume includes explicit guidance for setting up a program, implementing cognitively engaging physical games and learning activities, working effectively with mixed-age groups, and monitoring outcomes. Reproducible forms and lesson plans can be downloaded and printed in a convenient 8 1/2" x 11" size. "--Provided by publisher.